WAVELET TRANSFORM APPLIED IN ECG SIGNAL PROCESSING - Xhaja, Brikena; Kalluci, Eglantina; Nikolla, Ligor (European Scientific Journal, ESJ, 2015)
In this paper, we have introduced the compression of electrocardiogram (ECG) using a wavelet transformation. We will treat ECG as a signal and will implement a matched filter; and more precisely, the Wiener filter which is proportional to the signal itself. Also, we will use this filter to detect the positions of the heart beats. In this application, we will be using the white noise. However, the matched filter will not be proportional to the signal itself. Other results we have computed for this ECG signal are the mean difference of the heart beats and the heart rate. All these results are well–established diagnostic tools for cardiac diseases.